ПРОФЕСІЙНА САМОЕФЕКТИВНІСТЬ МАЙБУТНІХ ПЕДАГОГІВ У ГАЛУЗІ МИСТЕЦЬКОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2009)
The meaning of forming the pedagogical self-efficacy in the context of European integration, analyzing the influence of the professional self-efficacy' of the teacher on his self-regulatory and all kinds of work varieties when studying the students with the purpose of forming the pedagogical self-efficacy of the future teacher of music of the European rate are investigated in this article.